Assessment of potential kairomones and combination with the presence of insecticides in attracting Aedes aegypti (L.) (Diptera: Culicidae) - Ong, Song-Quan; Zairi Jaal (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
Kairomone play crucial role for Aedes aegypti (L) in the host seeking behaviour. Despite numerous researches had attempted kairomore in the formulation of “lethal lure”; however, lacking study of the interaction between the kairomore and lethal agent making the development of the strategy retard. In this study, attractiveness of selected kairomones and the effect of malathion and deltamethrin were tested in a modified single tunnel olfactometer. Ammonia-acetone and ammonia-acetic acid attracted significantly greater number of Ae. agypti and their attractiveness performed no significance different with the present of 5% of malathion impregnated paper; but demonstrated significantly lower attraction to mosquitoes when combined with 0.05% deltamethrin. This indicated malathion might be the suitable candidates for the formulation of lethal lure and future study should be focused on other possible lethal agent in combining with kairomones and field trial also required to test the efficiency of the formulation.